Chemoselective dithioacetalization of aldehydes using silica sulfuric acid as a reusable catalyst - Pore, D. M.; Desai, Uday V.; Mane, R. B.; Wadgaonkar, P. P. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2006)
Silica sulfuric acid has been found to be an efficient and reusable catalyst for chemoselective dithioacetalization of aldehydes over ketones, in excellent yields.
Keywords: Chemoselective; dithioacetalization; silica sulfuric acid

Efficient deprotection of dithioacetals to carbonyls using Oxone-KBr in aqueous acetonitrile - Desai, Uday V.; Pore, D. M.; Tamhankar, B. V.; Jadhav, Sushilkumar A.; Wadgaonkar, P. P. (Tetrahedron Letters, 2006)
A simple and efficient method has been developed for the chemoselective dethioacetalization of dithioacetals to aldehydes and ketones using Oxone-KBr in aqueous acetonitrile at room temperature. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: deprotection; dethioacetalization; Oxone

Efficient, solvent-free method for the chemoselective synthesis of acylals from aldehydes and their deprotection catalyzed by silica sulfuric acid as a reusable solid acid catalyst - Desai, Uday V.; Thopate, T. S.; Pore, D. M.; Wadgaonkar, P. P. (Catalysis Communications, 2006)
An efficient method has been developed for the chemoselective synthesis of acylals from aldehydes and acetic anhydride in the presence of silica sulfuric acid as a reusable solid acid catalyst under solvent-free conditions. Ketones are found to remain unaffected under the reaction conditions. The deprotection of acylals has also been achieved using SSA in methanol medium. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Acylals; aldehydes; Chemoselective; protection and deprotection silica sulfuric acid

Potassium phosphate or silica sulfuric acid catalyzed conjugate addition of thiols to alpha,beta-unsaturated ketones at room temperature under solvent-free conditions - Pore, D. M.; Soudagar, M. S.; Desai, Uday V.; Thopate, T. S.; Wadagaonkar, P. P. (Tetrahedron Letters, 2006)
Potassium phosphate and silica sulfuric acid have been found to be useful and highly efficient catalysts for conjugate addition of thiols to alpha,beta-unsaturated ketones under solvent-free conditions, at room temperature. Silica sulfuric acid (SSA) was found to be suitable for electron-deficient enones while potassium phosphate was found to effect thia-Michael addition with both, electron-deficient as well as electron-rich conjugated ketones. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: alpha; beta-unsaturated ketones; chalcones; conjugated enones; Michael addition; Potassium phosphate; silica sulfuric acid; thiols

Anhydrous magnesium sulfate mediated solvent-free synthesis of dihydropyrimidin-2(1H)-ones at ambient temperature - Pore, D. M.; Desai, Uday V.; Thopate, T. S.; Wadgaonkar, P. P. (Australian Journal of Chemistry, 2007)
An anhydrous magnesium sulfate mediated solvent-free protocol is described for the synthesis of dihydropyrimidinones (Biginelli compounds) at ambient temperature.

Sulfamic acid: an efficient and cost-effective solid acid catalyst for the synthesis of alpha-aminophosphonates at ambient temperature - Mitragotri, Satish D.; Pore, D. M.; Desai, Uday V.; Wadgaonkar, P. P. (Catalysis Communications, 2008)
Sulfamic acid catalyzed solvent-free protocol has been developed for the synthesis of alpha-aminophosphonates by three component condensation between aldehydes, amines and diethyl phosphite at ambient temperature. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: alpha-Aminophosphonates; diethylphosphite (DEP); solid acid catalyst; Solvent-free; sulfamic acid (SA)

Lithium tetrafluoroborate catalyzed highly efficient inter- and intramolecular aza-Michael addition with aromatic amines - Lad, Uday P.; Kulkarni, M. A.; Desai, Uday V.; Wadgaonkar, P. P. (Comptes Rendus Chimie, 2011)
Lithium tetrafluoroborate has been demonstrated for the first time to be an efficient catalyst in intermolecular aza-Michael addition aromatic amines to electron deficient alkenes. Suitability of the same catalyst in intramolecular aza-Michael addition leading 2-aryl-2,3-dihydroquinolin-4(1H) ones has also been described. (C) 2011 Published by Elsevier Masson SAS on behalf of Academie des sciences.
Keywords: 2-aryl-2; 3-dihydroquinolin-(4H)-1-ones; Anilines; Lithium tetrafluoroborate; Michael addition

Practical and highly efficient protocol for multicomponent synthesis of beta-phosphonomalononitriles and 2-amino-4H-chromen-4-yl phosphonates using diethylamine as a novel organocatalyst - Kulkarni, M. A.; Pandurangi, V. R.; Desai, Uday V.; Wadgaonkar, P. P. (Comptes Rendus Chimie, 2012)
Diethylamine has been demonstrated for the first time to be a highly efficient organocatalyst in the solvent-free synthesis of beta-phosphonomalononitriles by a three component condensation of aldehyde, malononitrile and dialkyl phosphite at ambient temperature. The applicability of the same catalyst in the synthesis of diethyl (2-amino-3-cyano-chromene-4-yl) phosphonic acid esters has also been described. (c) 2012 Published by Elsevier Masson SAS on behalf of Academie des sciences.
Keywords: 2-amino-4H-chromenes; beta-phosphonomalononitriles; diethylamine; multicomponent reactions; organocatalyst; Phospha-Michael reaction

Diethylamine: a smart organocatalyst in eco-safe and diastereoselective synthesis of medicinally privileged 2-amino-4H-chromenes at ambient temperature - Kulkarni, Makarand A.; Pandit, Kapil S.; Desai, Uday V.; Lad, Uday P.; Wadgaonkar, Prakash P. (Comptes Rendus Chimie, 2013)
Diethylamine has been demonstrated to be an efficient organocatalyst in the diastereoselective synthesis of Bcl-2 protein antagonist (HA-14-1) and of its structural analogues by one-pot condensation between salicylaldehyde and three different C-H acids, viz, ethyl cyanoacetate, phenylsulfonyl acetonitrile, and malononitrile. Easy commercial availability of the catalyst at extremely low cost and avoidance of conventional work-up as well as purification procedures qualifies this scalable protocol for a ``near-ideal synthesis''. (c) 2013 Academie des sciences. Published by Elsevier Masson SAS. All rights reserved.
Keywords: 2-amino-4H-chromenes; Active methylene compounds (C-H acids); diethylamine; multicomponent reactions; organocatalyst

Mechanistic approach for expeditious and solvent-free synthesis of alpha-hydroxy phosphonates using potassium phosphate as catalyst - Kulkarni, Makarand A.; Lad, Uday P.; Desai, Uday V.; Mitragotri, Satish D.; Wadgaonkar, Prakash P. (Comptes Rendus Chimie, 2013)
An extremely simple, high yielding, highly rapid and solvent-free protocol has been described for hydrophosphylation of aldehydes using potassium phosphate as catalyst. Easy commercial availability of the reusable catalyst, operational simplicity at ambient temperature and avoidance of conventional work-up as well as purification procedure makes this solvent-free protocol a near-ideal synthesis. (C) 2012 Academie des sciences. Published by Elsevier Masson SAS. All rights reserved.
Keywords: alpha-hydroxy phosphonates; Hydrophosphylation; Potassium phosphate; Solvent-free

Cellulose supported cuprous iodide nanoparticles (Cell-CuI NPs): a new heterogeneous and recyclable catalyst for the one pot synthesis of 1,4-disubstituted-1,2,3-triazoles in water - Chavan, Pramod V.; Pandit, Kapil S.; Desai, Uday V.; Kulkarni, Makarand A.; Wadgaonkar, Prakash P. (RSC Advances, 2014)
Cellulose supported cuprous iodide nanoparticles (Cell-CuI NPs) have been demonstrated for the first time as an efficient heterogeneous catalyst in the click synthesis of 1,4-disubstituted 1,2,3-triazoles by a one-pot three component reaction between aralkyl/alkyl bromides, alkynes and sodium azide in water. The catalyst has been characterized by XRD, HRTEM, SEM, ICP-AES, EDS as well as IR spectroscopy. It was found to be reusable for five consecutive runs without significant loss of activity.

Nickel ferrite nanoparticles-hydrogen peroxide: a green catalyst-oxidant combination in chemoselective oxidation of thiols to disulfides and sulfides to sulfoxides - Kulkarni, Aparna M.; Desai, Uday V.; Pandit, Kapil S.; Kulkarni, Makarand A.; Wadgaonkar, Prakash P. (RSC Advances, 2014)
Nickel ferrite nanoparticles-hydrogen peroxide has been demonstrated for the first time as a green and efficient catalyst-oxidant combination in the chemoselective oxidation of thiols to disulfides and sulfides to sulfoxides. This magnetically separable catalyst was found to be reusable for five consecutive runs without appreciable change in the activity, as well as composition of the catalyst. The mechanism for the oxidation of thiols and sulfides has also been proposed.

Simple, economical, and environmentally benign protocol for the synthesis of 2-amino-3,5-dicarbonitrile-6-sulfanylpyridines at ambient temperature - Desai, Uday V.; Kulkarni, Makarand A.; Pandit, Kapil S.; Kulkarni, Aparna M.; Wadgaonkar, Prakash P. (Green Chemistry Letters and Reviews, 2014)
A simple, economical, and environmentally benign protocol has been described for one-pot synthesis of medicinally privileged 2-amino-3,5-dicarbonitrile-6-sulfanylpyridines by three-component condensation between aldehyde, malononitrile, and thiol using diethylamine as a catalyst. Ambient temperature and avoidance of conventional work-up as well as purification procedure qualify this cost-effective protocol for ``green synthesis.''
Keywords: 5-dicarbonitriles; diethylamine; green chemistry; multicomponent reactions; organocatalyst; pyridine-3

Cobalt ferrite nanoparticles: a magnetically separable and reusable catalyst for Petasis-Borono-Mannich reaction - Kulkarni, Aparna M.; Pandit, Kapil S.; Chavan, Pramod V.; Desai, Uday V.; Wadgaonkar, Prakash P. (RSC Advances, 2015)
Magnetically separable cobalt ferrite nanoparticles (CoFe2O4, NPS) have been demonstrated for the first time as an efficient catalyst in Petasis-Borono-Mannich (PBM) reaction between salicylaldehydes, sec. amines and aryl boronic acids to furnish alkylaminophenols in high yields. Relatively shorter reaction times, easy purification of the products and reusability of the catalyst for five consecutive runs without appreciable loss in it's activity are the noteworthy features of the developed protocol.

Tris-hydroxymethylaminomethane (THAM): a novel organocatalyst for a environmentally benign synthesis of medicinally important tetrahydrobenzo[b]pyrans and pyran-annulated heterocycles - Pandit, Kapil S.; Chavan, Pramod V.; Desai, Uday V.; Kulkarni, Makarand A.; Wadgaonkar, Prakash P. (New Journal of Chemistry, 2015)
simple, efficient and environmentally benign protocol has been developed for the one-pot, multicomponent synthesis of medicinally important tetrahydrobenzo[b]pyrans and pyran-annulated heterocycles using a commercially available, inexpensive, non-toxic, and biodegradable tris-hydroxymethylaminomethane (THAM) as a novel organocatalyst. Ambient reaction conditions, wide scope, avoidance of conventional isolation as well as purification techniques and the reusability of the catalyst for five consecutive runs have improved the practical utility of this multicomponent reaction protocol manifold.

Diethylamine-catalyzed environmentally benign synthesis of 1-oxo-hexahydroxanthenes and bis-coumarins at ambient temperature - Kupwade, Ravindra V.; Pandit, Kapil S.; Desai, Uday V.; Kulkarni, Makarand A.; Wadgaonkar, Prakash P. (Research on Chemical Intermediates, 2016)
An extremely simple, economical and environmentally benign protocol has been described for one-pot synthesis of 1-oxo-hexahydroxanthenes by pseudo three-component condensation between salicylaldehydes and dimedone, cyclohexane-1,3dione or 5-methyl cyclohexane-1,3-dione using diethylamine as the catalyst. Based upon the mechanism of the reaction, the protocol has been extended towards the synthesis of tetraketones and bis-coumarins.

Problem solving and environmentally benign approach toward diversity oriented synthesis of novel 2-amino-3-phenyl (or Alkyl) sulfonyl-4H-chromenes at ambient temperature - Pandit, Kapil S.; Kupwade, Ravindra V.; Chavan, Pramod V.; Desai, Uday V.; Wadgaonkar, Prakash P.; Kodam, Kisan M. (ACS Sustainable Chemistry & Engineering, 2016)
A problem solving, environmentally benign, and diversity oriented protocol has been described for multi component synthesis of medicinally privileged 2-amino-3-phenyl (or methyl) sulfonyl-4H-chromenes by one-pot, three component condensation among aldehydes, phenyl (or methyl) sulphonyl acetonitrile, and alpha-naphthol, 3-dimethylamino phenol, 4-hydroxy-N-methyl-quinoline-2-one as well as 4-hydroxycarbazole, using diethylamine as an efficient organo catalyst. The catalyst employed is commercially available, inexpensive, and nontoxic. Ambient reaction conditions, very high yields, wide scope, and avoidance of conventional isolation as well as chromatographic purification have improved the practical utility of this protocol manifold.
Keywords: 2-Amino-3-methylsulfonyl-4H-chromenes; 2-Amino-3-phenylsulfonyl-4H-chromenes; diethylamine; green chemistry; Multicomponent synthesis; organocatalyst

Click-chemistry-based multicomponent condensation approach for design and synthesis of spirochromene-tethered 1,2,3-triazoles as potential antitubercular agents - Chavan, Pramod V.; Pandit, Kapil S.; Desai, Uday V.; Wadgaonkar, Prakash P.; Nawale, Laxman; Bhansali, Sujit; Sarkar, Dhiman (Research on Chemical Intermediates, 2017)

Diethylamine Dess-Martin periodinane: an efficient catalyst-oxidant combination in a sequential, one-pot synthesis of difficult to access 2-amino-3,5-dicarbonitrile-6-sulfanylpyridines at ambient temperature - Kupwade, Ravindra V.; Khot, Supriya; Kulkarni, M. A.; Desai, Uday V.; Wadgaonkar, Prakash P. (RSC Advances, 2017)
Herein, diethylamine Dess–Martin periodinane has been demonstrated for the first time as an efficient catalyst–oxidant combination in a sequential, one-pot synthesis of medicinally privileged but difficult to access 2-amino-3,5-dicarbonitrile-6-sulfanylpyridines via a pseudo-four component reaction between 2,6-disubstituted benzaldehydes, malononitrile, and thiols. Ambient reaction conditions, excellent yields, and total avoidance of conventional isolation as well as purification are the noteworthy merits of this developed protocol.

Sulfamic acid-catalyzed, environmentally benign synthesis of bis-tetronic acids at ambient temperature - Pandit, Kapil S.; Desai, Uday V.; Wadgaonkar, Prakash P.; Kodam, Kisan M. (Research on Chemical Intermediates, 2017)
An enviro-economic protocol has been described for the synthesis of bis-tetronic acids by pseudo-three-component condensation between aldehydes/isatins and tetronic acid using sulfamic acid as a solid acid catalyst. Easy commercial availability of the catalyst at extremely low cost, excellent yields and avoidance of conventional purification procedures are the main merits of this energy efficient protocol.

Tris-hydroxymethylaminomethane (THAM): An efficient organocatalyst in diversity-oriented and environmentally benign synthesis of spirochromenes - Khot, Supriya S.; Anbhule, Prashant V.; Desai, Uday V.; Wadgaonkar, Prakash P. (Comptes Rendus Chimie, 2018)
Tris-hydroxymethylaminomethane has been demonstrated to be an efficient organocatalyst in diversity-oriented synthesis of medicinally prevalent spirochromenes by one-pot, three-component reactions between isatins, malononitrile, and enolizable CH acids like dimedone, 4-hydroxycoumarin, 4-hydroxy-N-methylquinolin-2-one, or in situ generated 2-methylpyrazolon-2-one. Biodegradability and extremely low cost of the catalyst are the noteworthy features of this chromatography-free protocol.
Keywords: green chemistry; Multicomponent synthesis; organocatalysis; Spirochromenes; Tris-hydroxymethylaminomethane

Highly efficient and extremely simple protocol for the oxidation α-hydroxyphosphonates to α-ketophosphonates using Dess-Martin periodinane - Kupwade, Ravindra; Mitragotri, Satish D.; Kulkarni, Makarand A.; Desai, Uday V.; Wadagaonkar, Prakash P. (ARKIVOC, 2021)